1966
DOI: 10.1097/00007890-196611000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Serotyping for Homotransplantation V. Evaluation of a Matching Scheme

Abstract: SummaryAn attempt was made to determine whether 36 long-term kidney homograft recipients and their donors were compatible for 7 major leukocyte groups. It was found that 21 of these recipients were surviving 2 to 3 years in spite of incompatibility for 1 or 2 major leukocyte antigens. Survival of mismatched grafts does not itself indicate that the antigens being measured are not transplantation antigens, for it was shown that the 15 recipients with no groups of mismatch were clinically superior to those with g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
1

Year Published

1966
1966
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(27 citation statements)
references
References 11 publications
2
24
0
1
Order By: Relevance
“…More complete data were subsequently obtained from correlation of two year findings on biopsy in these same patients with the quality of the Terasaki match. These studies by Porter et al [25,27] indicated a high degree of correlation between the state of morphologic preservation of the renal homograft and the completeness of antigen matching.…”
Section: Histocompatibilitymentioning
confidence: 95%
“…More complete data were subsequently obtained from correlation of two year findings on biopsy in these same patients with the quality of the Terasaki match. These studies by Porter et al [25,27] indicated a high degree of correlation between the state of morphologic preservation of the renal homograft and the completeness of antigen matching.…”
Section: Histocompatibilitymentioning
confidence: 95%
“…To test this hypothesis, the antigenic mismatches of the donor-recipient pairs were compared to those which were obtained from control studies of a random population sample. 66 The most important data are those from the five living patients in whom homografts from nonrelated donors were employed; the results from these cases in comparison to those expected from random population matching between nonrelatives are summarized in Figure 20. In all five instances, the incidence of mismatches of those possible was 14.4 per cent or less.…”
Section: Antigen Analysis (Pt and Dlv)mentioning
confidence: 99%
“…The most completely characterized of these antibodies is detectable by virtue of its reactivity with a heterogenetic antigen found in sheep red cell stromata, which remains in the sheep cell membrane after the isophile component is removed by boiling (27). a series in which donors were selected prospectively by the Terasaki method on the basis of the best available match (33). The two others received cadaveric homografts in which it was not attempted to evaluate the biologic suitability of the donor in advance.…”
Section: Discussionmentioning
confidence: 99%